THE RELATIONSHIP BETWEEN SOCIO DEMOGRAPHIC CHARACTERISTICS WITH BREAST SELF EXAMINATION PRACTICES (BSE) IN FACULTY OF NURSING UNPAD STUDENTS - Novarina Ismayani Anumilah; Laili Rahayuwati; Ristina Mirwanti (Journal of Maternity Care and Reproductive Health, 2021)
BSE practice as an effort in detecting breast cancer needs to be emphasized in the fertile age group, especially students. One of the factors that influence BSE practice is socio demographic characteristics. The purpose of this study is to determine the relationship between socio demographic characteristics with BSE practice. The research design in this study was a correlational study. The sample in this study was 225 female students of the Faculty of Nursing UNPAD, with a stratified random sampling method. The instrument used in this research was a questionnaire of socio demographic characteristics and BSE practice. The results showed that only 22% of respondents had practiced BSE correctly. The results of bivariate analysis with Cramer’s V test showed that the year of grade of the respondents had a significant relationship with BSE practice (p = <0.05). While the score of the GPA, family history, ethnicity, religion, and family income were not found to be related (p = >0.05). The conclusion from this study is that BSE respondents' practice has a significant relationship with the respondent's grade years. Based on this, it is hoped that information related to BSE can also be given to freshman students who are just entering college and to further researchers, it is expected to expand the research field so that more variant results can be found.